The Effect of Concentric and Eccentric Exercise on Muscle Hardness - KUBOTA, ATSUSHI; FUJITA, SHIMPEI; KISHIMOTO, KOHEI; SAKURABA, KEISHOKU (Juntendo Iji Zasshi = Juntendo Medical Journal, 2018)
Objective: The purpose of this study was to investigate the effect of different contraction types on muscle structures, functions and muscle hardness. Materials: 6 healthy males (age: 22.8±1.5 years, height: 176.1±4.0 cm, weight: 72.3±11.0 kg) participated in this study.Methods: Subjects performed concentric contraction (CC) exercise of elbow flexor with one arm, and eccentric contraction (EC) exercise of elbow flexor with the other arm with the same total work. Muscle hardness of the biceps brachii measured by strain ratio, elbow joint angle, and maximal voluntary contraction (MVC) torque of elbow flexors were measured before (PRE), 1 hour (1H), 3 hours (3H) and 24 hours (24H) after the exercise protocol. Muscle soreness was measured at 1H, 3H, and 24H time points.Results: A significant interactions (time×type) was found in MVC torque (p<0.01), elbow joint angle (p<0.01), and muscle thickness (p=0.013). Strain ratio, MVC torque significantly decreased at 1H, 3H, and 24H compared to PRE after the EC exercise (p<0.05). Main effect in time was detected in Strain ratio (p=0.046) and upper arm circumference (p=0.044). Main effect in contraction type was detected in muscle soreness (p<0.01) with the greater level after the EC exercise. Elbow joint angle significantly increased at 1H, 3H, and 24H (p<0.05) compared to PRE after the EC exercise, and at 1H, 3H compared to PRE after the CC exercise (p<0.05). Upper arm circumference significantly increased at 1H compared to PRE after the CC exercise (p<0.05). Conclusions: The disruption of muscle function is greater and longer lasting after the eccentric contraction exercise than the concentric contraction exercise, and the muscle hardness only increased after the eccentric exercise when the exercises are performed with the same total work. The mechanisms of functional disruption following exercises and its effect on the muscle hardness may different according to the type of muscle contraction.